Changes in Walking Speed After High-Intensity Treadmill Training Are Independent of Changes in Spatiotemporal Symmetry After Stroke - Cleland, Brice; Madhavan, Sangeetha (Frontiers in Neurology, 2021)
Objectives: Decreased walking speeds and spatiotemporal asymmetry both occur after stroke, but it is unclear whether and how they are related. It is also unclear whether rehabilitation-induced improvements in walking speed are associated with improvements in symmetry or greater asymmetry. High-intensity speed-based treadmill training (HISTT) is a recent rehabilitative strategy whose effects on symmetry are unclear. The purpose of this study was to: (1) assess whether walking speed is cross-sectionally associated with spatiotemporal symmetry in chronic stroke, (2) determine whether HISTT leads to changes in the spatiotemporal symmetry of walking, and (3) evaluate whether HISTT-induced changes in walking speed are associated with changes in spatiotemporal symmetry. Methods: Eighty-one participants with chronic stroke performed 4 weeks of HISTT. At pre, post, and 3-month follow-up assessments, comfortable and maximal walking speed were measured with the 10-meter walk test, and spatiotemporal characteristics of walking were measured with the GAITRite mat. Step length and swing time were expressed as symmetry ratios (paretic/non-paretic). Changes in walking speed and symmetry were calculated and the association was determined. Results: At pre-assessment, step length and swing time asymmetries were present (p < 0.001). Greater temporal symmetry was associated with faster walking speeds (p ≤ 0.001). After HISTT, walking speeds increased from pre-assessment to post-assessment and follow-up (p ≤ 0.002). There were no changes in spatiotemporal symmetry (p ≥ 0.10). Change in walking speed was not associated with change in spatial or temporal symmetry from pre- to post-assessment or from post-assessment to follow-up (R2 ≤ 0.01, p ≥ 0.37). Conclusions: HISTT improves walking speed but does not systematically improve or worsen spatiotemporal symmetry. Clinicians may need to pair walking interventions like HISTT with another intervention designed to improve walking symmetry simultaneously. The cross-sectional relation between temporal symmetry and walking speed may be mediated by other factors, and not be causative.